(untitled) (Medical Forum Monthly, 2024)
Objective: This cross-sectional study aimed to compare the efficacy of these three treatments in managing TMJ disorders. Study Design: A retrospective study Place and Duration of Study: This study was conducted at the Abbasi Shaheed Hospital, Karachi from January 2023 to June 2024. Methods: A total of 60 patients diagnosed with TMJ disorders were recruited and divided into three equal groups of 20 patients. Data was collected using a structured questionnaire and clinical examination. The following information was recorded. Results: The Botox group demonstrated the most significant pain reduction, with a mean VAS score of 2.1 ± 0.9 at 3 months, compared to 4.5 ± 1.3 in the PRP group and 4.3 ± 1.2 in the HA group. The mean MMO increase was also highest in the Botox group (15.3 ± 3.6 mm), compared to 8.7 ± 4.3 mm in both the PRP and HA groups. Quality of life improvements were most notable in the Botox group, with a mean increase of 27.4 ± 9.1 points, significantly higher than the improvements seen in the PRP (17.3 ± 10.2) and HA (15.1 ± 9.8) groups. Conclusion: PRP, HA, and Botox are effective minimally invasive treatments for TMJ disorders. Botox may offer superior pain relief and functional improvement compared to PRP and HA.